EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DAN NUMBERED HEADS TOGETHER PADA MATERI POKOK FUNGSI DITINJAU DARI KECERDASAN INTERPERSONAL SISWA KELAS VIII SMP NEGERI SE-KOTA SURAKARTA - Zainuddin, Zainuddin; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this research were to determine: (1) which has better learning achievement, students are given TS-TS, NHT, or directÂ  intruction, (2)Â  which has better learning achievement, students with intrapersonal intelligence of high, medium or low, (3) which has better learning achievement, students with interpersonal intelligence of high, medium or low on each learning model, (4) which has better learning achievement, students are given TS-TS, NHT, and direct intruction on each interpersonal intelligence. This study was a quasi experimental research with 3 3 factorial design. The population of this study was all eighth grade students of junior high schools in Surakarta. Sampling was done by stratified cluster random sampling. The sample in this study are 271 people with details of 89 people for class experiment I, 91 people for class experiment II and 91 people for control class. The instruments used were mathematics achievement test andÂ  questionnaire of studentâs interpersonal intelligence. The data was analyzed using two ways anova. Based on the hypothesis test, it is concluded as follows. (1) Cooperative learning methods TS-TS type provide a better performance than cooperative learning method NHT type and direct intruction. (2) Mathematics learning achievements of students with high interpersonal intelligence levels did not differ from that of students with medium levels of interpersonal intelligence, while learning mathematics achievement of students with a high or medium level of interpersonal intelligence was better than that of students with low levels of interpersonal intelligence. (3) At each level of studentsâ interpersonal intelligence, TS-TS provided a better mathematics learning achievement compared with NHT learning and direct learning, while NHT learning provided no difference in mathematics learning achievement from direct learning. (4) At each learning model, mathematics learning achievement of students with high level of interpersonal intelligence was not different from that of students with medium level of interpersonal intelligence, while mathematics learning achievement of students with a high or medium level of interpersonal intelligence was better than that of students with low levels of interpersonal intelligence.Keywords: Two Stay Two Stray (TS-TS), Numbered Heads Together (NHT), Interpersonal Intelligence.